2022
DOI: 10.3389/fmolb.2022.965730
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of DCLK1 in cancer and cancer stem cells

Abstract: Doublecortin-like kinase 1 (DCLK1), a protein molecule, has been identified as a tumor stem cell marker in the cancer cells of gastrointestinal, pancreas, and human colon. DCLK1 expression in cancers, such as breast carcinoma, lung carcinoma, hepatic cell carcinoma, tuft cells, and human cholangiocarcinoma, has shown a way to target the DCLK1 gene and downregulate its expression. Several studies have discussed the inhibition of tumor cell proliferation along with neoplastic cell arrest when the DCLK1 gene, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 288 publications
0
8
0
Order By: Relevance
“…This is an important finding, since the mammalian homolog of ZYG-8 (DCLK1/doublecortin-like kinase 1) is upregulated in a wide range of cancers, and knockdown studies have suggested that it is required for tumor progression. Because of this, DCLK1 has recently become a target for the development of kinase inhibitors as therapeutics (Chandrakesan et al, 2017; Chhetri et al, 2022; Ferguson et al, 2020; Ge et al, 2021; Westphalen et al, 2017; Westphalen et al, 2016; Weygant et al, 2014) . However, whether kinase activity is essential for DCLK1’s function in cell division was not previously known.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding, since the mammalian homolog of ZYG-8 (DCLK1/doublecortin-like kinase 1) is upregulated in a wide range of cancers, and knockdown studies have suggested that it is required for tumor progression. Because of this, DCLK1 has recently become a target for the development of kinase inhibitors as therapeutics (Chandrakesan et al, 2017; Chhetri et al, 2022; Ferguson et al, 2020; Ge et al, 2021; Westphalen et al, 2017; Westphalen et al, 2016; Weygant et al, 2014) . However, whether kinase activity is essential for DCLK1’s function in cell division was not previously known.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that DCLK1 could serve as a potentially favorable target for addressing pancreatic cancer. [77] [78]…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that DCLK1 could serve as a potentially favorable target for addressing pancreatic cancer. [77] [78] CTNNB1, also referred to as beta-catenin, is a pivotal protein participating in regulating cell adhesion and transcriptional activity of genes. Mutations in the CTNNB1 gene have been detected in diverse cancer forms., including pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has revealed that many genes and proteins are abnormally expressed in cancer cells and contribute to cancer progression by regulating cell growth, proliferation, apoptosis, migration, and metastasis 12,13 . Otubain 2 (OTUB2), a deubiquitinase belonging to ovarian tumor (OTU) superfamily, 14 was first discovered in an OTU gene from Drosophila melanogaster 15 .…”
Section: Introductionmentioning
confidence: 99%
“…and metastasis. 12,13 Otubain 2 (OTUB2), a deubiquitinase belonging to ovarian tumor (OTU) superfamily, 14 was first discovered in an OTU gene from Drosophila melanogaster. 15 As proven by previous studies, OTUB2 exerts oncogenic effects in human cancers.…”
mentioning
confidence: 99%